2019
DOI: 10.1139/cjc-2018-0505
|View full text |Cite
|
Sign up to set email alerts
|

“Acid spike” formation in the fast neutron radiolysis of supercritical water at 400 °C studied by Monte Carlo track chemistry simulations

Abstract: A reliable understanding of radiolysis processes in supercritical water (SCW) cooled reactors is required to ensure optimal water chemistry control. In this perspective, Monte Carlo track chemistry simulations of the radiolysis of pure, deaerated SCW at 400 °C by 2 MeV mono-energetic neutrons were carried out as a function of water density between 0.15 and 0.6 g/cm3. The yields of hydronium ions (H3O+) formed at early time were obtained based on the G values calculated for the first three generated recoil prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…35 We calculated the yields (or G-values) 36 and the concentrations of radiolytically formed H 3 O + and the corresponding pH values that prevailed in these track regions immediately after irradiation as a function of time for both low and high LET, 16,25 at ambient and elevated temperatures, 37 even under supercritical conditions. 38,39 In all cases studied, an abrupt, transient acidspike response was observed around the "native" radiation tracks. This response is a very sensitive function of radiation quality (LET) and temperature.…”
Section: The Early Transitory Acidic Ph Responsementioning
confidence: 92%
“…35 We calculated the yields (or G-values) 36 and the concentrations of radiolytically formed H 3 O + and the corresponding pH values that prevailed in these track regions immediately after irradiation as a function of time for both low and high LET, 16,25 at ambient and elevated temperatures, 37 even under supercritical conditions. 38,39 In all cases studied, an abrupt, transient acidspike response was observed around the "native" radiation tracks. This response is a very sensitive function of radiation quality (LET) and temperature.…”
Section: The Early Transitory Acidic Ph Responsementioning
confidence: 92%
“…This example provides a clear illustration of how water's pH might vary in the early stages of radiolysis under varying dose rate conditions, specifically at a nominal pressure of 25 MPa. Our prior studies [16,32,33] have shown that the initial acidic response in water exposed to high-LET radiation is markedly more significant than that observed with low-LET radiation. Conversely, using 300 MeV protons as a representative model to evaluate acidic spikes in SCWRs and SMRs can be seen as a cautious approach, particularly in terms of the actual magnitude of the effect.…”
Section: Resultsmentioning
confidence: 87%